Customer service expectations in retail banking in Africa - G. Bick; R. Abratt; D. Möller (South African Journal of Business Management, 2010)
There has been very little research on customer service in the African continent. This paper determines and analyses customer service expectations of 4035 clients in retail banking across 10 African countries. In addition country differences in customer service expectations are identified. A quantitative research design was followed. Bank customers in banking halls were intercepted and interviewed about their service expectations at their bank. The survey instrument used was a questionnaire developed from the SERVQUAL model. A comparative scaling technique applying a partial rank order scale was used. The results show customer service expectations differ significantly between countries in Africa. Overall in Africa the dimension `responsiveness' was the most important service requirement for retailing bank customers, followed by `reliability of service'. However, when analysing results by country clear differences and similarities emerge. It is important for Banks to take cross-national differences into consideration when designing and implementing a global marketing strategy, or even a Pan-African marketing strategy. Relational Issues surrounding assurance and empathy are of less importance in an African context.
Keywords: 650